Snails found among herbarium specimens of Galapagos lichens and bryophytes, with the description of Scolodonta rinae (Gastropoda: Scolodontidae), a new species of carnivorous micro-mollusk - Miquel, Sergio Eduardo (2017)
For the first time we document several species of micro-mollusks in the Galapagos inhabiting lichens and bryophytes, possibly using them as part of their diet. Eight species of mucro-mollusks were found as a by-cath among 10% of 400 herbarium specimens collected troughout the archipelago. Nine species of lichens and 6 of bryophytes were inhabited. Another snail found is a predator, Scolodonta rinae n. sp. (Scolodontidae).